PANDANGAN MASYARAKAT TERHADAP BERIANG (KAWIN LARI) AKIBAT TINGGINYA BELIS DITINJAU DARI HUKUM ISLAM (Studi Kasus di Desa Nampar Sepang Kecamatan Sambi Rampas Kabupaten Manggarai Timur NTT) - Hajanawati; Rahma Amir; Muhammad Fajri (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam)
The main problem of this research is the community's view of the briang in Nampar Sepang Village, Sambi Rampas District, East Manggarai Regency and the implementation process as well as the views of Islamic law on the briang. This research is a qualitative research with three approaches, namely syar'i, juridical and sociological. The results of this study indicate that briang marriage in Nampar Sepang Village has become one of the traditions or habits that are often practiced by the community. Briang is a way out of a relationship that does not get the blessing, promiscuity and/or pregnancy out of wedlock, and is unable to pay very high belis. There are several community leaders who do not agree with the existence of this briang tradition, namely religious leaders, traditional leaders, community leaders, KUA officials and many other Nampar Sepang people, because they are considered to deviate from Islamic teachings in general. Although this briang marriage is legal according to religion as long as it fulfills the requirements and pillars of marriage, the impression is not good for people, families and society.